1982
DOI: 10.1073/pnas.79.17.5430
|View full text |Cite
|
Sign up to set email alerts
|

Post-tetanic potentiation at an identified synapse in Aplysia is correlated with a Ca2+-activated K+ current in the presynaptic neuron: evidence for Ca2+ accumulation.

Abstract: We have examined the presynaptic changes underlying post-tetanic potentiation (PTP) in Aplysia by using voltage-clamp techniques combined with specific pharmacological blocking agents. The amplitude and time course of PTP parallel a slow outward clamp current that we have identified as a Ca2+_ activated K+ current. Because this current is proportional to intracellular Ca2+ concentration our findings provide evidence for the "residual Ca2+ hypothesis," according to which PTP is caused by the accumulation of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 27 publications
3
36
0
Order By: Relevance
“…For example, studies in the squid giant synapse have demonstrated that BAPTA attenuates neurotransmitter release, while EGTA has no effect (19,20). At the same time, however, EGTA is effective in preventing PTP (21). It is thought that EGTA fails to affect transmitter release for the same reason that it is less effective than BAPTA in preventing Ca2+-dependent inactivation of Ca2+ channels-i.e., its time constant of Ca2+ binding is too slow.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies in the squid giant synapse have demonstrated that BAPTA attenuates neurotransmitter release, while EGTA has no effect (19,20). At the same time, however, EGTA is effective in preventing PTP (21). It is thought that EGTA fails to affect transmitter release for the same reason that it is less effective than BAPTA in preventing Ca2+-dependent inactivation of Ca2+ channels-i.e., its time constant of Ca2+ binding is too slow.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experiments on the squid stellate ganglion synapse (112) show that an alteration of Ca 2+ current of sufficient amplitude to cause facilitation would have been readily detected. Experiments on Aplysia neuron L10 show a close correspondence between facilitation and internal calcium as measured by the activity of the Ca 2+ -dependent K + channel (122). The kinetics of disappearance of facilitation are thought to be regulated by the time course of Ca 2+ removal (126).…”
Section: Biochemical Nature Of the Ca 2+ Channel-progress In Camentioning
confidence: 93%
“…REGULATION OF THE CALCIUM CHANNEL-All types of short-term synaptic plasticity that have been investigated in detail involve modulation of Ca 2+ levels in the terminals, though the mechanisms differ (121,122). The amount of Ca 2+ -influx during an action potential is primarily regulated by the opening and closing of Na + and K + channels (e.g.…”
Section: Biochemical Nature Of the Ca 2+ Channel-progress In Camentioning
confidence: 99%
See 1 more Smart Citation
“…These features have many parallels with another kind of short-term plasticity, called "paired-pulse facilitation" [73]. Paired-pulse facilitation is thought to be caused chiefly by the residual elevation of the intracellular calcium concentration ([Ca 2+ ] i ) in presynaptic terminals [73,74] (Figure 14D). …”
Section: Otolaryngolmentioning
confidence: 95%